2011
DOI: 10.1002/pros.21350
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β1‐induced EMT of non‐transformed prostate hyperplasia cells is characterized by early induction of SNAI2/Slug

Abstract: This study suggests that in BPH-1 cells the transcription factor SNAI2/Slug is important for EMT initiation, while the ZEB family of transcription factors in cooperation with the miR-200 family may oppose the reversal of the EMT phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 45 publications
(56 reference statements)
5
72
0
Order By: Relevance
“…The main molecular factors triggering EMT are the nuclear factor κB pathway [11], the Wnts signaling pathway [12], the transforming growth factor β 1 pathway [13,14], the integrin family members [15,16], and the activation of receptor tyrosine kinases [4]. The central target of these signaling pathways is the repression of E-cadherin expression and the increase of vimentin expression.…”
Section: Discussionmentioning
confidence: 99%
“…The main molecular factors triggering EMT are the nuclear factor κB pathway [11], the Wnts signaling pathway [12], the transforming growth factor β 1 pathway [13,14], the integrin family members [15,16], and the activation of receptor tyrosine kinases [4]. The central target of these signaling pathways is the repression of E-cadherin expression and the increase of vimentin expression.…”
Section: Discussionmentioning
confidence: 99%
“…In PC-3 prostate cancer cells, blockade of NF-kB signaling leads to decreased vimentin expression and inhibition of their invasive capability, indicating functional involvement of NF-kB in mediating TGF-b-induced EMT [50]. Other transcription factors, such as SNAI2/Slug that control E-cadherin expression (epithelial cell marker), are causally involved in TGF-b1-induced EMT in non-transformed prostate cells, conferring loss of polarity at the invading front [51]. In benign epithelial cells, EMT transcriptional inducers, Snail and Twist, contribute to the appearance of CD44Hi/CD24low cancer stem cells phenotype, implicating EMT as the process driving acquisition of stemlike characteristics in cancer cells [52].…”
Section: Landscape Design By Tgf-b: Epithelialemesenchymal Transitionmentioning
confidence: 97%
“…TGF-β1 is a cytokine that enhances cell characteristics associated with invasiveness, metastasis and motility (14,16). EMT is associated with progression and poor prognosis in various types of cancer, and can be induced by TGF-β1 (14). In a study by Koo et al (15), AY-27 rat bladder cancer cells were incubated with TGF-β1 and were observed to have reduced E-cadherin and increased vimentin immunoreactivity.…”
Section: Discussionmentioning
confidence: 96%
“…This may be a novel mechanism of invasion and metastasis in bladder cancer. TGF-β1 is a cytokine that enhances cell characteristics associated with invasiveness, metastasis and motility (14,16). EMT is associated with progression and poor prognosis in various types of cancer, and can be induced by TGF-β1 (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation